Zufallsbefunde im Röntgenthorax - Wielpütz, Mark Oliver; Kauczor, Hans-Ulrich; Weckbach, Sabine (Der Radiologe, 2017)
Conventional projection radiography (chest x‑ray) is one of the most frequently requested procedures in radiology. Even though chest x‑ray imaging is frequently performed in asymptomatic patients for preoperative assessment, clinically relevant incidental findings are relatively scarce. This is due to the relatively low sensitivity of chest x‑rays where few clinically relevant incidental findings are to be expected, as any detectable pathologies will as a rule already be clinically symptomatic. Recommendations from relevant societies for the management of incidental findings, apart from the clarification of incidental nodules, do not exist. This review article therefore describes the most frequent and typical incidental findings of lung parenchyma (apart from pulmonary nodules), mediastinal structures including the hilum of the lungs, pleura, chest wall and major vessels. Also described are those findings which can be diagnosed with sufficient certainty from chest x‑rays so that further clarification is not necessary and those which must be further clarified by multislice imaging procedures or other techniques.